Redesigning animal agriculture [ the challenge of the 21st century - Swain, David L. (CABI, 2007)
Focusing on livestock production systems, this text addresses how the diversity of global food demands will be met in future, providing insights into scientific areas and the implications for addressing global drivers for change.